Ball milling – a new concept for predicting degradation profiles in active pharmaceutical ingredients. Issue 90 (27th October 2021) - Kaiser, Reinhard P.; Krake, Everaldo F.; Backer, Laura; Urlaub, Jonas; Baumann, Wolfgang; Handler, Norbert; Buschmann, Helmut; Beweries, Torsten; Holzgrabe, Ulrike; Bolm, Carsten
Abstract : Forced oxidative mechanochemical degradation of clopidogrel hydrogensulfate as a model compound leads to selective formation of degradants in less than 15 minutes. Abstract : A method for forced oxidative mechanochemical degradation of active pharmaceutical ingredients (APIs) using clopidogrel hydrogensulfate as a model compound is presented. Considerable and selective formation of degradants occurs already after very short reaction times of less than 15 minutes and the nature of the products is strongly dependent on the used oxidant.